No, You Wouldn’t Want to Not Read this Paper: a working paper on a typology of negation across the romance languages - Fleming, Bryan; Belko, Danielle; Nagengast, Jeffrey (Lingua Frankly, 2016)
In this paper, we discuss negation in several languages of the same family—languages which are strikingly similar in many aspects but which use varying strategies to form negatives. We begin our discussion by describing Rafaella Zanuttini's investigation into the typology of Romance languages in terms of how negation is formed. We follow with a more detailed description of negation strategies in several widely spoken romance languages, viz., Spanish, Italian, and French—bringing in information from other dialects when useful or interesting. Next, we attempt to discuss Zanuttini's typology vis-à-vis the corpora of data we have in the aforementioned languages, citing the (in)compatibility/(non-)compliance of these languages with her typological descriptions. Lastly, we discuss some historical insight into why these differences exist and follow that with descriptions of languages and dialects not referenced in Zanuttini's article. We also discuss any trends that these languages exhibit in relation to Zanuttini's generalizations.